MOTIVATING STUDENTS TO SPEAK THROUGH CONTEXTUAL TEACHING LEARNING - Muhammad Shabir (Fakultas Keguruan Ilmu Pendidikan Universitas Ibn Khaldun Bogor, 2018)
This study investigated students‟ motivation in speaking through Contextual Teaching Learning (CTL) at a junior high school in Bogor, West Java. The procedures of action research: plan, act, observe, reflect, and revise were used to investigate the participants‟ learning activities and motivation. The study was conducted in two cycles involving two on-site English teachers. Data were collected through the teacher’s journal, observers‟ sheets, students‟ diaries, and questionnaires. The results of the research indicated that students‟ motivation in speaking could be improved through exposure to a variety of learning activities that connect the learning activities to the students‟ lives and experiences. Finally, the results of the study are expected to have a contribution to developing students to be motivated language learners.